Dexmedetomidine and Ketamine Attenuated Neuropathic Pain Related Behaviors via STING Pathway to Induce ER-Phagy - Liu, Yongda; Kuai, Shihui; Ding, Mengmeng; Wang, Zhibin; Zhao, Limei; Zhao, Ping (Frontiers in Synaptic Neuroscience, 2022)
Our previous work indicated that ER-phagy level had altered in spinal nerve ligation (SNL) rats. In this study, we investigated whether dexmedetomidine or ketamine exhibits anti-anxiety or anti-nociceptive effects via modulation of the spinal STING/TBK pathway to alter ER-phagy in SNL rats. We evaluated the analgesic and anti-anxiety effects of ketamine and dexmedetomidine in SNL rats. 2'3'-cGAMP (a STING pathway agonist) was administrated to investigate whether enhanced spinal STING pathway activation could inhibit dexmedetomidine or ketamine treatment effects in SNL rats. Analgesic effects were assessed with the mechanical withdrawal threshold (MWT) and anti-anxiety effects were measured via an open field test (OFT). Protein expression levels were evaluated by immunoblotting. Distribution and cellular localization of Grp78 (ER stress marker) were evaluated by confocal immunofluorescence. SNL induced mechanical hypersensitivity and anxiety in rats; dexmedetomidine and ketamine both provided analgesia and anti-anxiety effects in SNL rats. Furthermore, the STING pathway was involved in the modulation of ER stress and ER-phagy in SNL rats and dexmedetomidine and ketamine alleviated ER stress by inhibiting STING pathway to enhance ER-phagy. Thus, both ketamine and dexmedetomidine provided anti-anxiety and anti-nociceptive effects by alleviating ER stress through the inhibition of the STING/TBK pathway to modulate spinal ER-phagy in SNL rats.